Public space in the city: An approximation from hedonic prices - Araque Solano, Alex Smith; Gutiérrez López, Julián Alberto; Quenguan López, Lina Fernanda (Sociedad y Economía, 2017)
This document is the result of an applied research to the park system in Bogota, which aims to propose an econometric model for determining the value of the public space land. Given the complexity of valuing public land, the research was developed by combining the determinants of social choice theory by means of Arrow’s impossibility theorem and the price model (by emphasizing urban structure). The Department of Public Space Advocacy, of Bogotá achieved as a main result, that there is a high social value of the public space, placing as challenge the incorporation of more refined economic analyzes to describe the different value criteria that the society makes of the public space. It was also found that presence of public spaces in the urban context, strongly influence the determination of private land prices.